Equity valuation : Marriott International, Inc. - Guerra, João Caria Henriques (2019)
This dissertation aims to value the equity of Marriott International, Inc. (MAR), the world’s largest hospitality company. A variety of methodologies that can be applied in equity valuation will be presented, out of which a Discounted Cash Flow approach using Free Cash Flow to the Firm (FCFF), along with an analysis using Price and Enterprise multiples, will be the preferred ones. An in-depth overview of the Tourism and Hospitality industries will also be provided. The information used and the analyses developed are laid out in the main part of the dissertation, which allows for the issue of a HOLD recommendation with a target price of $124.03/share for December 31st, 2019. Sensitivity and scenario analyses are also carried out, and they allow for a clearer understanding of how the target price can be influenced by key valuation parameters. Through the use of Price and Enterprise multiples, a valuation range between $136.71 and $119.77 is obtained. The conclusions obtained and processes followed were then compared against a report issued by SunTrust Robinson Humphrey, which issued a HOLD recommendation with a target price of $131.00.